Correction: One-shot carboxylation of microcrystalline cellulose in the presence of nitroxyl radicals and sodium periodate. Issue 117 (11th November 2015) - Coseri, Sergiu; Biliuta, Gabriela; Zemljič, Lidija Fras; Srndovic, Jasna Stevanic; Larsson, Per Tomas; Strnad, Simona; Kreže, Tatjana; Naderi, Ali; Lindström, Tom
Abstract : Correction for 'One-shot carboxylation of microcrystalline cellulose in the presence of nitroxyl radicals and sodium periodate' by Sergiu Coseri et al., RSC Adv., 2015, 5, 85889–85897.